1978
DOI: 10.1097/00000658-197806000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of the Esophagus

Abstract: Spontaneous rupture of the esophagus remains a medical and surgical challenge. Its diagnosis is often missed or delayed resulting in increased morbidity and mortality, and controversy exists as to the mode of therapy for the cases seen later than 12 hours after rupture. During the last seven years, nine patients were treated at Grady Memorial Hospital. Four patients, "early group," were operated upon within 12 hours from the onset of their symptoms and five, "late group," were operated upon between 20-76 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Diagnostic errors are prevalent; the most common misdiagnosis is perforated ulcer, followed by myocardial infarction, pulmonary embolism, dissecting aneurysm and pancreatitis [7, 8]. Diagnosis can be made earlier and more accurate with additional radiological examinations such as CT scan [9] (fig.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic errors are prevalent; the most common misdiagnosis is perforated ulcer, followed by myocardial infarction, pulmonary embolism, dissecting aneurysm and pancreatitis [7, 8]. Diagnosis can be made earlier and more accurate with additional radiological examinations such as CT scan [9] (fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most common misdiagnosis is perforated ulcer, myocardial infarction, pulmonary embolism, dissecting aneurysm and pancreatitis [8,9]. In our data collective, thirteen patients were undergone unnecessary exploration surgery because of initial diagnostic mistakes and most often it was done in hospitals with inadequate clinical experience in thoracic surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In general, although high, overall mortality rates for esophageal perforations are decreasing with new advances in surgical care and improved recognition of this condition 13 . 14 Early diagnosis of esophageal perforations may reduce mortality rates because studies comparing early intervention (<24 h) have demonstrated improved survival compared with late treatment (>24 h) 11 , 15 –20 …”
Section: Review Of Mortality and Morbidity Associated With Spontanmentioning
confidence: 99%